Bean germplasm conservation based on seed drying with silica gel and low moisture storage - Fischler, MA (International Center for Tropical Agriculture, 1993)
Preservation of germplasm collections with low temperature storage is problematic because of power failures and equipment breakdown. Low moisture storage is an alternative to low temperature storage for medium-term germplasm conservation of seeds of most crops. Seed drying using silica gel for medium-term storage of bean seed was investigated. Seeds of two bean cultivars were dried for 50 days with silica gel in a desiccator experiment using a gel to seed ratio of 1:2. The final moisture content was 6.1 and 6.6 percent for the two cultivars. Dry seeds were stored in recycled glass soda bottles with screw caps sealed with candle wax at 25 degrees C for one year. The seed moisture content remained constant confirming that recycled glass soda bottles can be used as inexpensive seed storage containers. Germination rates after one year of storage were 97.5 and 100 percent for the two cultivars. It is expected that the seed can be kept in glass bottles for 10-20 years (mid-term storage). In order to dry larger amounts of seed, a drying facility using silica gel in an air-tight PVC drum was developed. Procedures were developed for collection, characterization and maintenance of bean germplasm collections, as well as for data management.